1.92k likes | 2.02k Views
CHAPTER 2 RevIEw. precalculus. y = (x+2) 2. y = (x-2) 2 -1. y = -(x+1) 2 + 3. 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s 2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour.
E N D
CHAPTER 2 RevIEw precalculus
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth. 59.4 MPH
5) f(x) = x2 - 16 = (x )(x )
5) f(x) = x2 - 16 = (x - 4)(x + 4)
5) f(x) = x2 - 16 = (x - 4)(x + 4) zeros: 4, -4
6) f(x) = x2 + 12x + 36 = (x )(x )
6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6)
6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6) zeros: -6, -6
7) f(x) = 2x2 - 14x + 24 = 2( )
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12)
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x )(x )
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3)
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3) zeros: 4, 3
8) f(x) = x4 - x3 - 20x2 = x2( )
8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x)
8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x )(x )
8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x + 4)(x - 5)
8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5)
8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5) zeros: 0, 0, -4, 5
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2)
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) • (x + 7)(x - 2)
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) • (x + 7)(x - 2) • x2 - 2x + 7x - 14
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) • (x + 7)(x - 2) • x2 - 2x + 7x - 14 • x2 + 5x - 14
10) 0, 4 (x - 0)(x - 4)
10) 0, 4 (x - 0)(x - 4) x(x - 4)
10) 0, 4 (x - 0)(x - 4) x(x - 4) x2- 4x
What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right
What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right
What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right
12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right
12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right
12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right
13) f(x) = 6(x4 + 3x2 + 2)rises to the left rises to the right falls to the left falls to the right
13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right
13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right